In vivo imaging xenograft models for the evaluation of anti‐brain tumor efficacy of targeted drugs. (10th November 2017) - Kita, Kenji; Arai, Sachiko; Nishiyama, Akihiro; Taniguchi, Hirokazu; Fukuda, Koji; Wang, Rong; Yamada, Tadaaki; Takeuchi, Shinji; Tange, Shoichiro; Tajima, Atsushi; Nakada, Mitsutoshi; Yasumoto, Kazuo; et al.
Abstract: Molecular‐targeted drugs are generally effective against tumors containing driver oncogenes, such as EGFR, ALK, and NTRK1 . However, patients harboring these oncogenes frequently experience a progression of brain metastases during treatment. Here, we present an in vivo imaging model for brain tumors using human cancer cell lines, including the EGFR ‐L858R/T790M‐positive H1975 lung adenocarcinoma cells, the NUGC4 hepatocyte growth factor (HGF)‐dependent gastric cancer cells, and the KM12SM colorectal cancer cells containing the TPM3‐NTRK1 gene fusion. We investigated the efficacy of targeted drugs by comparison with their effect in extracranial models. In vitro, H1975 cells were sensitive to the third‐generation epidermal growth factor receptor inhibitor osimertinib. Moreover, HGF stimulated the proliferation of NUGC4 cells, that was inhibited by crizotinib, which has anti‐MET activity. KM12SM cells were sensitive to the tropomyosin‐related kinase‐A inhibitors crizotinib and entrectinib. In in vivo H1975 cell models, osimertinib inhibited the progression of both brain and subcutaneous tumors. Furthermore, in in vivo NUGC4 cell models, crizotinib remarkably delayed the progression of brain tumors, and that of peritoneal carcinomatosis. Interestingly, in in vivo KM12SM cell models, treatment with crizotinib delayed the progression of liver metastases, but not that of brain tumors. Conversely, treatment with entrectinib discernibly delayed the progression of both tumor types. Thus, the effect of targeted drugs against brain tumors can differ from the one reported in extracranial tumors. Moreover, the same multikinase inhibitory drug can display different efficacies in brain tumor models containing different drivers. Therefore, our in vivo imaging model for brain tumors may prove useful for preclinical drug screening against brain metastases. Abstract : We present an in vivo imaging model for brain tumors using human cancer cell lines, including the EGFR ‐L858R/T790M‐positive H1975 lung adenocarcinoma cells, the NUGC4 hepatocyte growth factor (HGF)‐dependent gastric cancer cells, and the KM12SM colorectal cancer cells containing the TPM3‐NTRK1 gene fusion. We investigated the efficacy of targeted drugs by comparison with their effect in extracranial models, and found that the same multikinase inhibitory drug can display different efficacies in brain tumor models containing different drivers. Therefore, our in vivo imaging model for brain tumors may prove useful for preclinical drug screening against brain metastases.